Mycobacterium tuberculosis and the host cell inflammasome: a complex relationship - Briken, Volker; Ahlbrand, Sarah E.; Shah, Swati (Frontiers in Cellular and Infection Microbiology, 2013)
The production of IL-1β during the infection with Mycobacterium tuberculosis (Mtb) is important for successful host immune defense. In macrophages and dendritic cells the host cell inflammasome is crucial for generation of secreted IL-1β in response to Mtb infections. In these cell types Mtb infection only activates the NLRP3-inflammasome. New reports demonstrate that nitric oxide has an important function in the negative regulation of the NLRP3-inflammasome to reduce tissue damage during Mtb infections. The type I interferon, IFN-β, is induced after Mtb infections and can also suppress NLRP3-inflammasome activation. In contrast, IFN-β increases activity of the AIM2-inflammasome after infection with intracellular pathogens such as Francisella tularensis and Listeria monocytogenes. Recent results demonstrate that non-tuberculous mycobacteria but not virulent Mtb induce the AIM2-inflammasome in an IFN-β dependent matter. Indeed, Mtb inhibits AIM2-inflammasome activation via its ESX-1 secretion system. This novel immune evasion mechanism may help Mtb to allow the induction of low levels of IFN-β to suppress the NLRP3-inflammasome without activating the AIM2-inflammasome.